A Response to "Arguments Against the Core Area Hypothesis" for Plant Domestication. (November 2013) - G, A; L -, S; A, S
Abstract : The paper relates to several issues concerning geographical and chronological aspects of the 'core area' model for plant domestication in the Levant (Lev- Yadun et al . 2000), as presented in Fuller et al . (2011). The paper stresses that the core area as depicted by Fuller et al . does not correspond to the original core area map and list of Neolithic sites published by the authors (Lev-Yadun et al . 2000). It also discusses the alternative model suggested by Fuller et al ., namely the alleged existence of autonomous, independent domestication centres in the Levant, a suggestion that does not conform to the available archaeobotanical, as well as genetic and archaeological data. A primarily technical section on chronology considers the procedures used by Fuller and his associates concerning 14 C dating. Archaeobotanical data inconsistencies are also noted.